Enzalutamide monotherapy in hormone-naive prostate cancer: primary analysis of an open-label, single-arm, phase 2 study - Tombal, Bertrand; Borre, Michael; Rathenborg, Per; Werbrouck, Patrick; Van Poppel, Hendrik; Heidenreich, Axel; Iversen, Peter; Braeckman, Johan; Heracek, Jiri; Baskin-Bey, Edwina; Ouatas, Taoufik; Perabo, Frank; et al. (Lancet oncology, 2014)
BACKGROUND: The androgen receptor inhibitor enzalutamide is approved for the treatment of metastatic castration-resistant prostate cancer that has progressed on docetaxel. Our aim was to assess the activity and safety of enzalutamide monotherapy in men with hormone-naive prostate cancer. METHODS: This trial is an ongoing open-label, single-arm, phase 2 study, done across 12 European sites. Men aged over 18 years, with hormone-naive prostate cancer for whom hormone therapy was indicated, and who had non-castration levels of testosterone and prostate-specific antigen (PSA) of 2 ng/mL or greater at screening, and an Eastern Cooperative Oncology Group score of 0, received oral enzalutamide 160 mg/day. The primary outcome was the proportion of patients with an 80% or greater decline in PSA at week 25. All analyses included all patients who had received at least one dose of the study drug. This study is registered with ClinicalTrials.gov, number NCT01302041. FINDINGS: 67 men were enrolled into the study. 62 patients (92.5%, 95% CI 86.2-98.8) had a decline in PSA of 80% or greater at week 25. The most commonly reported treatment-emergent adverse events up to week 25 were gynaecomastia (n=24), fatigue (n=23), nipple pain (n=13), and hot flush (n=12), all of which were of mild to moderate severity. Nine patients had a treatment-emergent adverse event of grade 3 or higher, most of which were reported in one patient each, except for pneumonia (grade 3, two patients) and hypertension (grade 3, four patients). Five patients reported serious adverse events, none of which were deemed to be treatment related. INTERPRETATION: Our findings suggest that enzalutamide monotherapy in men with hormone-naive prostate cancer of varying severity provides a level of disease suppression, and was generally well tolerated. These findings provide a rationale for further investigation of clinical response and outcomes with enzalutamide in non-castrate men with prostate cancer.
Keywords: senioři nad 80 let; Humans; lidé středního věku; Antineoplastic Agents; Aged, 80 and over; Middle Aged; protinádorové látky; fenylthiohydantoin; Prostate-Specific Antigen; mužské pohlaví; antagonisté androgenů; Adenocarcinoma; prostatický specifický antigen; nádory prostaty; výsledek terapie; Androgen Antagonists; Prostatic Neoplasms; Treatment Outcome; Phenylthiohydantoin; lidé; Aged; senioři; Male; adenokarcinom